PENGELOLAAN SUMBER DAYA INSANI DALAM MEMASARKAN PRODUK DAN JASA LEMBAGA KEUANGAN SYARIAH - Muhammad Isa, S.T., M.M (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2016)
Now, bank and islamic financial institutions are growing rapidly. They must show their differences from the conventional institutions one. It is the fact that most of Indonesian Moslems feel there is nothing special differences between islamic financial institutions and conventional institutions. They conclude it from their expriences. This perception is not good for development of islamic financial institutions in the future. So, we must restore the policies about islamic financial institutions management. One of them is about human resource. The employees must good in character, masteries in fiqh muamalah, islamic financial knowledge, computers, etc. They must have commitment to practise islamic economy in their activities